2011
DOI: 10.1093/cid/ciq249
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Recurrence Following Falciparum and Mixed Species Malaria: Risk Factors and Effect of Antimalarial Kinetics

Abstract: On the Thai-Myanmar border, Plasmodium vivax is the most common cause of parasitological failure following treatment for acute falciparum malaria. Slowly eliminated antimalarials significantly reduce the risk of early recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
158
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(170 citation statements)
references
References 31 publications
10
158
2
Order By: Relevance
“…For example, recurrences, presumed to be relapses, occur earlier following artemether-lumefantrine than following dihydroartemisininpiperaquine or artesunate-mefloquine, because lumefantrine is eliminated more rapidly than either mefloquine or piperaquine. This same temporal pattern of recurrence with particular drugs is seen in the P. vivax infections that follow up to a third of acute falciparum malaria infections in South-East Asia (21,22).…”
Section: Principlesmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, recurrences, presumed to be relapses, occur earlier following artemether-lumefantrine than following dihydroartemisininpiperaquine or artesunate-mefloquine, because lumefantrine is eliminated more rapidly than either mefloquine or piperaquine. This same temporal pattern of recurrence with particular drugs is seen in the P. vivax infections that follow up to a third of acute falciparum malaria infections in South-East Asia (21,22).…”
Section: Principlesmentioning
confidence: 57%
“…Hypnozoites also appear to be activated by a febrile illness, such as that caused by another malaria episode (which may also indicate suitable transmission conditions) (19,20). Where both P. falciparum and P. vivax occur, an episode of P. falciparum malaria is frequently followed by episodes of P. vivax malaria (21,22).…”
Section: Host Geneticsmentioning
confidence: 99%
“…The emergence of CQ resistance in many endemic regions, along with > 50% prevalence of hypnozoites of P. vivax in patients diagnosed and treated for P. falciparum, provides a strong rationale for a unified policy for therapy of uncomplicated malaria of any species. 127,128 Hence, many of the schizontocidal drugs under development are now routinely tested against both dominant species of plasmodia. 129 In general, those with high potency against multidrug-resistant P. falciparum are also efficacious against P. vivax.…”
mentioning
confidence: 99%
“…A 2011 study on the Thai-Myanmar border confirmed that, because P. vivax may be unrecognized in P. falciparum infection, the "most commonly transmitted parasite after treatment for falciparum malaria, paradoxically, was not P. falciparum , but P. vivax ." 4 The use of primaquine for any of these indications is limited, however, by its hemolytic toxicity in G6PD-deficient patients. At least 200 G6PD genetic variants are known 5 and are classified according to the phenotype.…”
Section: Introductionmentioning
confidence: 99%